2009
DOI: 10.1177/1741659009335724
|View full text |Cite
|
Sign up to set email alerts
|

Naming, shaming and criminal justice: Mass-mediated humiliation as entertainment and punishment

Abstract: Shame has long been a dubious tool of criminal justice and has been carried on by state authorities in a variety of ways through the ages. However, since the latter part of the 20th century, humiliation has become amplified through the mass media in the name of crime control and entertainment. This article situates mass-mediated humiliation within broader trends in criminal justice and popular culture. While the enactment of humiliation via popular culture works powerfully within prevailing cultural beliefs ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 33 publications
0
50
0
1
Order By: Relevance
“…Through the association of particular groups, such as illegal immigrants, with risk and danger, and the representation of state agents as 'heroic' protectors, state agendas are effectively legitimised. For Kohm (2009), reality TV can constitute part of broader social control and criminal justice apparatus at a real as well as an ideological level. Using the example of NBC's Dateline: To Catch A Predator (a programme in which journalists, local police and an internet watchdog group use hidden cameras to lure, trap, confront and in many cases arrest suspected paedophiles), he contends that the message is two-fold: first, that 'communities are under attack and the only way to fight back is to be perpetually on the lookout for crime' and second, that the mass media can be seen as a 'private sector solution to the "law and order" crisis' (Kohm, 2009: 194).…”
Section: Resultsmentioning
confidence: 99%
“…Through the association of particular groups, such as illegal immigrants, with risk and danger, and the representation of state agents as 'heroic' protectors, state agendas are effectively legitimised. For Kohm (2009), reality TV can constitute part of broader social control and criminal justice apparatus at a real as well as an ideological level. Using the example of NBC's Dateline: To Catch A Predator (a programme in which journalists, local police and an internet watchdog group use hidden cameras to lure, trap, confront and in many cases arrest suspected paedophiles), he contends that the message is two-fold: first, that 'communities are under attack and the only way to fight back is to be perpetually on the lookout for crime' and second, that the mass media can be seen as a 'private sector solution to the "law and order" crisis' (Kohm, 2009: 194).…”
Section: Resultsmentioning
confidence: 99%
“…Examples cited include boot camps, three strikes legislation, increased use of execution, chain gangs, and a number of other policies relating to the public disclosure of off ences once an individual has been released from prison (primarily sexual and/or violent off ences). Together these polices have been termed 'shame penalties' (Karp 1998 ) or 'expressive extra-legal sanctions' (Pratt 2000 ), with Kohm ( 2009 ) suggesting that the primary goal of such policies is to humiliate the off ender while simultaneously affi rming the legitimacy of state power. Furthermore, Altheide ( 1992 ) argues that the more emotive styles of punishing have primarily gained their meaning through media discourse, with the portrayal of shame penalties in popular culture indicating a more general shift in public sensibilities, a shift which is characterised by an increased desire to celebrate cruelty, hurt and humiliation (Kohm 2009 ;Presdee 2000 ).…”
Section: Narratives Of Vengeancementioning
confidence: 99%
“…Th e spectacle of punishment and the fears associated with vulnerability become framed as entertainment; humiliation, vindictiveness and vengeance are positioned at the centre of crime and punishment cultural narratives (Bauman 2006 ;Kohm 2009 ;Lynch 2004 ;Presdee 2000 ;Sarat 1999a ). In short, within the cultural life of punishment, narratives of fear and vengeance are not mutually exclusive and one is often employed to (re)affi rm the necessity of the other.…”
Section: Narratives Of Vengeancementioning
confidence: 99%
“…If the video is made available to the public, the offender and officer may be shamed by the media and the public. Kohm (2009) identified that "shame and humiliation in criminal justice have become increasingly commodified, enacted, and experienced through hybrid forms of media that blur the boundaries of reality and entertainment" (p. 188).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This negative publicity can have an offender labeled a criminal for life or destroy an officer and their departments' credibility for years to come. Kohm (2009) recognized that this form of humiliation "has emerged in recent years as a viable and symbolically rich vehicle for social control when commodified and refracted through the lens of popular culture, the outcomes are unpredictable and may contain the seeds of discontent." (p. 189).…”
Section: Theoretical Frameworkmentioning
confidence: 99%